First trimester maternal tobacco smoking habits and fetal growth. Issue 3 (24th March 2010) - Prabhu, Nanda; Smith, Norman; Campbell, Doris; Craig, Leone C; Seaton, Anthony; Helms, Peter J; Devereux, Graham; Turner, Stephen W
Abstract : Rationale: Maternal smoking in pregnancy is associated with reduced birth weight and childhood lung function. This study determined when maternal smoking first influences fetal growth and how this relates to childhood respiratory outcomes. Methods: A longitudinal cohort of 1924 pregnant women was recruited. Fetal ultrasound measurements at 11 weeks (crown–rump length, CRL) and at 20 weeks gestation (femur length, FL, and biparietal diameter, BPD) and birth measurements were recorded. Childhood respiratory symptoms and spirometry were ascertained. Results: Of the 1924 original study participants, fetal size was determined in 903 in the first trimester, 1544 in the second trimester and at term in 1737 infants. Maternal smoking when first pregnant was reported in 593 (31%) and was not associated with reduced CRL. There was an inverse exposure-response relationship between cigarette consumption and FL (mean reduction in lowest compared with highest tertile 0.91 cm, p=0.033). Birth weight and length of those born to mothers who did (n=331) and did not (n=56) reduce cigarette consumption were similar and reduced compared with 186 infants whose mothers quit during the first trimester (p≤0.020). Children of mothers who continued smoking had increased wheeze at age 2 years (OR 1.58, p=0.017) and GP visits with wheeze at age 5 years (OR 2.18, p=0.030) and mean reduction in forced expiratory volume in 1 s of 62 ml (p=0.014) compared with controls. Conclusions: Maternal smoking is associated with reduced fetal measurements in the second and third trimesters but not in the first trimester. Mothers who do not quit smoking during the first trimester deliver smaller infants who go on to have adverse respiratory outcomes in childhood.